Analysis and calculation of higher harmonics of power supply system of plant on basis of packet wavelet conversion - S. A. Gorovoy; A. V. Simakov; V. I. Skorokhodov (Омский научный вестник, 2022)
After analyzing the results of physical tests of the power supply system of the plant, it is found that the values of individual harmonic components exceed the values established by GOST-32144 2013. Based on the data obtained, a simulation model is formed and an analysis of higher harmonics is performed using the packet wavelet transform method. The aim of the work is the analysis and calculation of higher harmonics and additional losses from them in the neutral conductor based on the packet wavelet transform method. The simulation is carried out using the Simulink software package. As a result of the study, it is found that the packet wavelet transform with high accuracy allows to determine the presence of higher harmonics in the power supply system, the efficiency of using the wavelet transform to calculate additional losses in the neutral conductor is shown.